ANALISIS KEPUASAN DAN KEPENTINGAN PELANGGAN TERHADAP KINERJA PELAYANAN DI PT.GREATWAYS ENGINEERING SERVICE DENGAN METODE SERVQUAL, IMPORTANCE PERFORMANCE ANALYSIS, DAN QUALITY FUNCTION DEPLOYMENT - Ahmad Hasymi Kurniawan (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2013)
This study aims to determine the service attributes that customers expect PT. GREATWAYS SERVICE ENGINEERING services in order to improve the previous system. The data because there is a decreased demand, the company will perform the analysis of the decline in demand, from enterprise data last 3 months there is a complaint of services performed by an employee or technician PT. GREAT WAYS ENGINEERING SERVICE, among other complaints are, hours of service are not timely, not timely report delivery, inspection is incomplete or unresolved. With respect to these problems, the research performed using Service Quality (ServQual), Importance Performance Analysis, Quality Function Deployment which aims to determine the attributes and services of interest to consumer satisfaction.